2017
DOI: 10.3892/ijmm.2017.3292
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate inhibits inflammation and epithelial‑mesenchymal transition through the PI3K/AKT pathway via upregulation of PTEN in asthma

Abstract: Asthma is a chronic disease associated with hyper-responsiveness, obstruction and remodeling of the airways. Epithelial-mesenchymal transition (EMT) has an important role in these alterations and may account for the accumulation of subepithelial mesenchymal cells, thus contributing to airway hyperresponsiveness and remodeling. Epigallo-catechin-3-gallate (EGCG), which is a type of polyphenol, is the most potent ingredient in green tea, and exhibits antibacterial, antiviral, antioxidative, anticancer and chemop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…Recently, numerous studies have investigated the protective effects of EGCG against asthma and other lung diseases such as COPD and lung pneumonia. EGCG may suppress inflammation and inflammatory cell infiltration into the lungs of asthmatic mice, and may also inhibit epithelial-mesenchymal transition EMT via the PI3K/Akt signaling pathway through upregulating the expression of phosphatase and tensin homolog (PTEN), both in vivo and in vitro [81].…”
Section: Other Dietary Constituents and Lung Infectionsmentioning
confidence: 99%
“…Recently, numerous studies have investigated the protective effects of EGCG against asthma and other lung diseases such as COPD and lung pneumonia. EGCG may suppress inflammation and inflammatory cell infiltration into the lungs of asthmatic mice, and may also inhibit epithelial-mesenchymal transition EMT via the PI3K/Akt signaling pathway through upregulating the expression of phosphatase and tensin homolog (PTEN), both in vivo and in vitro [81].…”
Section: Other Dietary Constituents and Lung Infectionsmentioning
confidence: 99%
“…Accordingly, these data identified PTEN as an endogenous defender against inflammation-mediated cellular damage in nasal epithelial cells. Previous studies have also illustrated the beneficial role of PTEN in acute kidney injury (28), diabetes (71), cardiomyopathy (72) and chronic fatty liver disease (73). Therefore, an approach to reverse PTEN activity could be considered as adjuvant therapy to enhance anti-inflammatory treatments in patients with chronic nasal and sinus inflammation, but this needs to be investigated further.…”
Section: Discussionmentioning
confidence: 97%
“…PTEN functions as a tumor suppressor involving in the regulation of the cell growth and differentiation (27). Previous studies have demonstrated that PTEN upregulation provides a survival advantage to nasal epithelial cells in asthma (28). Furthermore, pharmacological PTEN inhibition amplifies acute kidney injury (29,30), regulates inflammation-induced migration of myelocytes in zebrafish (31), and impacts nuclear factor-κB inflammatory pathways (32).…”
Section: Pten Enhances Nasal Epithelial Cell Resistance To Tnfα-inducmentioning
confidence: 99%
“…At present, it mainly focuses on inflammation, immune response changes and airway remodeling caused by abnormal subepithelial myofibroblasts and chronic inflammation. Studies have shown that abnormalities in multiple signaling pathways in lung tissue involve the development and progression of asthma, such as the PI3K/Akt, MAPK, ERK, JAK and c-Jun (El-Hashim et al, 2017;Li et al, 2015;Southworth et al, 2018;Wagh et al, 2017;Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, many studies have shown that activation of the PI3K/Akt pathway plays an important role in the development of asthma by activating oxidative stress and inflammatory responses (Wagh et al, 2017;Yang et al, 2018). The serine/threonine kinase Akt, also known as PKB (protein kinase B), is activated by lipid products of phosphatidylinositol 3kinase (PI3K).…”
Section: Introductionmentioning
confidence: 99%